2021
DOI: 10.3390/diagnostics11030577
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Strength Changes in Trabecular Bone in Elderly Patients with Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases worldwide and it is associated with an increased risk of osteoporosis and fragility fractures. Our aim is to analyze the effect of T2DM on bone quality. This is a case-control study. The studied population consisted of 140 patients: 54 subjects with hip fracture (OP) without T2DM, 36 patients with hip fracture and T2DM (OP-T2DM), 28 patients with osteoarthritis (OA) without T2DM, and 22 patients with OA and T2DM (OA-T2DM). Bone markers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A trabecular bone is a large-surface bone widely exposed to blood flow and bone marrow that is differentially influenced by several biochemical factors, including hormones and drugs, and with a higher turnover compared to dense cortical bone [ 7 ]. For these reasons, the metabolic imbalance can easily lead to its microarchitectural deterioration and worsening of mechanical properties [ 62 , 63 ]. TBS, determined from lumbar spine DXA images, reflects qualitative aspects of the skeletal structure, providing an indirect index of trabecular microarchitecture that is partially independent of, but complementary to, BMD [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A trabecular bone is a large-surface bone widely exposed to blood flow and bone marrow that is differentially influenced by several biochemical factors, including hormones and drugs, and with a higher turnover compared to dense cortical bone [ 7 ]. For these reasons, the metabolic imbalance can easily lead to its microarchitectural deterioration and worsening of mechanical properties [ 62 , 63 ]. TBS, determined from lumbar spine DXA images, reflects qualitative aspects of the skeletal structure, providing an indirect index of trabecular microarchitecture that is partially independent of, but complementary to, BMD [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the evolution of fractures describes the existence of complications in the consolidation period related to smoking or age ( 37 ) although, loss of bone minerals or diabetes highly influence the process. The most recent evidence ( 18 , 20 , 22 , 38 ) have pointed out that the bone tissue of diabetic patients presents loss of collagen ( 21 ), a high percentage of AGE advanced glycation products and a worse quality of trabecular bone which could compromise, in addition, its mechanical properties ( 20 , 39 ). Our results showed that bone consolidation time was similar between diabetic and non-diabetic patients (see Table 1 ), achieving a solid and effective consolidation in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have described deleterious effects of diabetic hyperglycemia on bone tissue quality ( 17 ), for example fragility or energy absorption ( 18 ), changes in trabecular volume and thickness ( 19 ) as well as mechanical properties ( 20 ) in addition to variants in the properties of collagen, minerals, and AGEs (advanced glycation products) ( 20 , 21 ). The accumulation of these diabetic exposure changes in bone cell activity could impair consolidation and long-term progenitor cell potential and may create vascular deficiencies at the fracture site ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, post-hip fracture mortality is higher in T2DM patients, with an increased risk of death up to 44% in the first year after the event ( 3 ). While the contribution of T2DM to low bone density is still debated, it is recognized that the longer the disease duration, the higher the trabecular bone microarchitecture and mechanical properties damage ( 4 ). Moreover, the combination of both T2DM-related intrinsic (i.e., vision impairment and loss of balance due to neuropathy and retinopathy complications) and extrinsic factors (for example, treatment-induced hypoglycemia), confers to the diabetic older patient an increased likelihood of falls, which are well-known to be associated with poor outcomes in advanced age ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%